Nuclear and Star Formation Activities in Nearby Galaxies: Roles of Gas Supply and Active Galactic Nucleus Feedback - Huynh Anh N. Le; Yongquan Xue (The Astrophysical Journal)
We analyze a sample of  ~113,000 galaxies ( z  < 0.3) from the Sloan Digital Sky Survey, divided into star-forming, composite, Seyfert, and LINER types, to explore the relationships between UV-to-optical colors ( u – r ), star formation rates (SFRs), specific SFRs (sSFRs), stellar velocity dispersions ( σ _* ), mass accretion rates onto the black hole ( ${L}_{[{\rm{O}}\,{\rm{III}}]}/{\sigma }_{\ast }^{4}$ ), and Eddington ratios. Star-forming galaxies predominantly feature young, blue stars along the main-sequence (MS) line, while composite, Seyfert, and LINER galaxies deviate from this line, displaying progressively older stellar populations and lower SFRs. The ${L}_{[{\rm{O}}\,{\rm{III}}]}/{\sigma }_{\ast }^{4}$ and Eddington ratios are highest in Seyfert galaxies, moderate in composite galaxies, and lowest in LINERs, with higher ratios associated with bluer colors, indicating a younger stellar population and stronger active galactic nucleus (AGN) activity. These trends suggest a strong correlation between sSFRs and Eddington ratios, highlighting a close connection between AGN and star formation activities. These results may imply an evolutionary sequence where galaxies transition from blue star-forming galaxies to red LINERs, passing through the composite and Seyfert phases, driven primarily by gas supply, with AGN feedback playing a secondary role. While both the radio luminosities ( L _1.4 GHz ) and Eddington ratios correlate with SFRs, their trends differ on the SFR−stellar-mass ( M _* ) plane, with the radio luminosities increasing with stellar mass along the MS line and no direct connection between the radio luminosities and Eddington ratios. These findings may provide new insights into the interplay between star formation, AGN activity, and radio emission in galaxies, shedding light on their evolutionary pathways.